Reversing the cytotoxicity of uric acid by supramolecular encapsulation with acyclic cucurbit[n]uril. (3rd March 2021) - Kong, Lingguang; Liang, Jing; Yang, Lei; An, Shu; Gao, Chuanzhu; Liao, Xiali; Zhao, Yulin; Yang, Bo
Abstract: Supramolecular encapsulation, which removes harmful substances from organisms, has evolved into a new strategy. In this paper, three supramolecular complexes of acyclic cucurbit[ n ]urils (ACBs) with uric acid (UA) were prepared, and the inclusion behavior of ACBs and UA was studied by fluorescence spectroscopy, UV–vis spectroscopy and nuclear magnetic resonance. Furthermore, the effect of the complexes of UA with ACBs on the expression of inflammatory biomarkers in human hepatoma HepG2 cell lines was characterized through C-reactive protein (CRP) western blot. The results showed UA molecules can be recognized by three ACBs with different binding constants, and ACBs successfully blocked the inflammatory stimulation of UA on HepG2 cell lines and inhibited the expression of the major inflammatory factor CRP by the formation of complexes between UA and ACBs. This article proves that ACBs can efficiently reverse the cytotoxicity of UA, which provides a new method for treating hyperuricemia disease.